(untitled) (Iraqi Journal of Medical Sciences, 2025)
Background:Nevi of Ota is usually present at birth. It may be congenital but is not hereditary. Objective :To determine the efficacy and side effect profile of Q-switched Nd:YAG and KTP Laser on fourteen patients with nevus of Ota. Methods: Fourteen patients were treated with Q-switched ND: YAG (1064 nm) and KTP (532 nm) laser for a period of 21 months. Six-month follow-up was done after the last session. Response to the treatment was graded on quartile grading scale. Results:Near total improvement was observed (grade IV) in 36% patients, marked improvement (grade III) in 28.5%, moderate improvement (grade II) in 28.5%, and minimal improvement (grade I) in 7% of the patients. Regarding complication (not permanent), no textural change or scaring. When Nd:YAG laser was only used to treat nevi of Ota for three sessions the response was less than 10% improvement in the lesion. When KTP used in combination with Nd-YAG alternatively there was an increasing improvement in most cases up to more than (70%). Conclusion:Concurrent use of the Q-switched 532 in combination with the (1064 nm) Nd:YAG is more effective in pigment clearance than the Q-switch (1064 nm) alone for nevus of Ota. Keywords:Nevus of Ota, Q-switched Nd:YAG (neodymium-doped yttrium aluminum garnet).